Use of Multimedia in PAI Learning at Muhammadiyah Kupang Vocational School - Mandasia Samsudin; Bambang Sumardjoko; Muhammad Wildan Shohib (al-Afkar, Journal For Islamic Studies, 2024)
The purpose of this study was to examine the learning of Islamic Religious Education by using multimedia and the obstacles in learning Islamic religious education at Muhammadiyah Kupang Vocational High School. The type of research used in this research is descriptive qualitative research. Descriptive research is research that aims to describe a symptom, event, or incident that is happening now. The approach used is qualitative. Qualitative research examines the perspective of participants with interactive and flexible strategies. While data collection techniques through observation, interviews, and documentation. After the collected data is analyzed by analyzing data reduction, presenting data and drawing conclusions. The results of this study indicate that: the teacher uses multimedia technology such as video players, pictures, power points as well as computer/laptop technology and telecommunication technology, the teacher carries out the PAI learning process according to the learning theory lesson plans. The obstacles faced by teachers are that teachers must be extra in supervising the use of information and communication technology. Besides that, teachers who are too old must always upgrade their knowledge regarding the use of multimedia.